GENETIC DIVERSITY AND CHARACTERIZATION OF PSEUDERANTHEMUM LATIFOLIUM BY RAPD AND ISSR MOLECULAR MARKERS - S. T. Bui; T. T. Khong; V. T. Ho (Journal of Animal and Plant Sciences, 2022)
Pseuderanthemum palatiferum is a commonly used ornamental plant in Vietnam. It is getting more attention due to its medicinal values. In this study, the genetic composition of 16 P. palatiferum accessions and relatives collected from Vietnam were analyzed using 16 RAPD and ISSR molecular markers. The obtained results show that both RAPD and ISSR produced a high number of polymorphic bands. The similarity coefficient varies among RAPD and ISSR, from 0.53 – 0.95 and 0.32 – 0.91, respectively. Mantel test also shows poor correlation between RAPD and ISSR markers. Both data from RAPD markers or combination of RAPD and ISSR markers could differentiate P. palatiferum from its relatives. The obtained results reveal the large variation in genetic composition of P. palatiferum population in Vietnam. The findings could be beneficial in classification, identification, and conservation efforts of P. palatiferum.
Keywords: Genetic diversity; ISSR; molecular markers; Pseuderanthemum palatiferum; RAPD